Prognosis of Very Low-Birth Weight Infants - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1990)
The cognitive and motor abilities of 43 very low birth weight children (VLBW) and classroom controls are reported from the Greenwood Children's Centre, City Hospital, Nottingham, England.